Reconstruction of Criminal Liability Against Digital Platforms in Cases of Human Trafficking in the Virtual World - Mgs Royhan Arief; Nurwijoyo Satriyo Aji Martono; Ahmad Ma'mum Fikri (JUSTISI, 2026)
The study aims to critique the shortcomings in the TPPO Law and ITE Law, which do not yet regulate strict liability for digital platforms. Therefore, this study focuses on analyzing the importance of criminal liability reform and the integration of due diligence principles and progressive sanctions for digital platforms. The method used in this study is a normative juridical approach, focusing on the analysis of legal norms relevant to the issues of digital human trafficking and corporate responsibility. The novelty of this study provides further insight into the reform of the criminal liability system and the integration of the principles of due diligence and progressive sanctions for digital platforms. The results of the study show that the involvement of digital platforms in human trafficking has become a serious challenge in the digital age, where technology is used for online recruitment, coordination, and exploitation of victims. Although Law Number 21 of 2007 concerning the Eradication of Criminal Acts of Trafficking in Persons (TPPO Law) regulates aspects of human trafficking, this regulation does not explicitly stipulate the responsibility of digital platforms, creating a legal loophole that is exploited by criminals. Therefore, in this case, The concluded findings of this study indicate that reform of the criminal liability system is necessary by integrating the principle of due diligence, which requires technology companies to take preventive measures such as user identity verification, artificial intelligence-based content monitoring, and reporting suspicious activities to the authorities. In addition, the application of progressive sanctions, such as fines proportional to company revenue or operational restrictions for negligent platforms, can increase corporate accountability.